KEBERFUNGSIAN AGAMA DALAM KELUARGA BEDA AGAMA PERSPEKTIF PENDIDIKAN AGAMA ISLAM - Mahsun Mahsun; Nur Budi Handayani; Khamim Saifuddin (Widyadewata, 2023)
Abstrak Artikel ini berangkat dari ketertarikan melihat fenomena keluarga beda agama ditinjau dari perspektif pendidikan agama Islam. Tujuannya untuk mengetahui: (1) fungsi keluarga dalam perspektif pendidikan Islam; (2) pola asuh pendidikan agama dalam keluarga; (3) pengaruh keluarga beda agama terhadap pendidikan agama anak. Penelitian ini merupakan studi kepustakaan. Sumber data berasal dari pustaka yang terkait dengan topik penelitian, terdiri atas primer dan sekunder. Data dikumpulkan dengan aplikasi Publish and Perish berbasis meta data google scholar dan scopus, dalam rentang waktu 10 tahun terakhir. Dari hasil penelitian diketahui (1) keluarga berfungsi sebagai lembaga pendidikan yang pertama dan utama. Konsepsi ideal keluarga sakinah menjadi landasan utama penyelenggaraan pendidikan dalam keluarga yang betujuan membentuk anak beriman, bertakwa, cakap dan berakhak mulia; (2) Keberfungsian agama (religious function) merupakan berlangsungnya pengasuhan keagamaan dan terjaganya nilai agama di dalam keluarga, melalui pengenalan adanya Tuhan, pembiasaan ibadah, dan pengajaran perilaku baik kepada anak; (3) Terdapat tiga praktek pendidikan agama dalam keluarga beda agama yaitu pertama, anak diajari dua agama orang tuanya; kedua, anak diajari salah satu agama orang tuanya; dan ketiga, orang tua membagi agama anaknya. Orang tua beda agama mengakibatkan erosi identitas agama anak. Kata Kunci: Agama Islam; Keluarga beda agama; Pendidikan; Pola asuh Abstract This article departs from an interest in seeing the interfaith families phenomenon based on perspective of Islamic religious education. The aim is to find out: (1) the function of the family in the perspective of Islamic education; (2) religious education parenting style in the family; (3) the influence of different religious families on children's religious education. This research is a literature study. Collecting data come from literature related to the research topic, consisting of primary and secondary. Data was collected using the Publish and Perish application based on Google Scholar and Scopus meta data, within the last 10 years later. The results are (1) that the family functions as the first and foremost educational institution. The ideal conception of a sakinah family is the main basis for organizing education in the family which aims to form children who are faithful, pious, capable and have noble character; (2) The function of religion (religious function) is the ongoing religious upbringing and maintenance of religious values ​​in the family, through the introduction of the existence of God, habituation of worship, and teaching good behavior to children; (3) There are three practices of religious education in families of different religions, namely first, children are taught the two religions of their parents; secondly, children are taught one of the religions of their parents; and third, parents divide the religion of their children. Parents of different religions result in the erosion of the child's religious identity. Keywords: Islamic religious; Interfaith marriage; Education; Parenting